STUDI KOMPARATIF PERUBAHAN PENDAPATAN USAHA WARUNG TRADISIONAL SEBELUM DAN SESUDAH ADANYA WARUNG RETAIL MODERN DI KECAMATAN MEDAN TIMUR - Sri Endang Rahayu; Halimun - Rambe (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2014)
Formulation of the problem in this paper is whether there is a change to thetraditional stalls operating revenues before and after the introduction of modernretail shop. This study aims to determine how changes in traditional stallsoperating revenues before and after the introduction of modern retail shop. Datacollection techniques in this study is a questionnaire (questionnaire), interview(interview). While the data analysis techniques used to interpret the data isobtained, allocate, analyze and organize the interpretation so as to provide a realpicture of the problem at hand. Results of this study was a decrease in revenues oftraditional stalls in view of the profit and sales turnover